ANALISIS PRINSIP KEADILAN DALAM AKAD BAGI HASIL PEMILIK KEBUN KARET DAN PENYADAP DI NAGARI SIGUNTUR KECAMATAN SITIUNG KABUPATEN DHARMASRAYA - Devianti, Regina; Alfin, Aidil (Jurnal Ekonomi Sakti, 2024)
An agreement that controls how the parties involved divide the money made is known as a profit-sharing agreement. As per the original agreement, workers and the fund provider will receive a part in the earnings, if they are substantial. If a loss does transpire, though, it must be shared by all. The purpose of this study is to comprehend the profit-sharing arrangements that tappers and proprietors of rubber plantations in Nagari Siguntur, Sitiung District, Dharmasraya Regency, engage in. In addition, the goal of this study is to investigate the fairness principles found in profit-sharing arrangements at the same site. In order to examine the concepts of justice, this study use qualitative methodologies. In Nagari Siguntur, Sitiung District, Dharmasraya Regency, the research was carried out. Techniques for gathering data include interviews, documentation, and observation. Conversations